Assessment of cerebrovascular reserve in unilateral middle cerebral artery stenosis using perfusion CT and CO2 inhalation tests. (3rd April 2017) - Yang, Fen; Shi, Wenqian; Shi, Jin; Zhang, Yingqian; Yin, Yanwei; Shi, Huiping; Chen, Dawei
Abstract : Purpose/Aim of the study: Cerebrovascular reactivity (CVR) is an important marker for assessing cerebrovascular disease. This study assessed the CVR by perfusion computed tomography (CT) and CO2 inhalation tests in patients with unilateral middle cerebral artery (MCA) stenosis disease. Materials and Methods: Thirty-one patients with unilateral MCA stenosis disease diagnosed by digital subtraction angiography were studied. Patients were divided into two groups according to the degree of stenosis: severe and moderate. The regional cerebral blood flow (CBF) before and after CO2 inhalation was determined by perfusion CT. Regional CVR values were obtained by the following formula: increase (%) = (post-CBF) − (pre-CBF)/(pre-CBF) × 100%. Results: No significant differences in the mean CBF in the MCA stenosis region were found between the affected and contralateral sides before the CO2 inhalation test; after the test, CBF was more significantly decreased on the affected side than on the contralateral side. The changes in CBF on the affected side were categorized into three types: increased CBF (17 cases), decreased CBF (12 cases) and no change in CBF (2 cases). The rate of CVR impairment among severe stenosis patients (13/19) was higher than that among moderate stenosis patients (3/12). CVR was significantly correlated with the degree of stenosis ( r = 0.423, P = 0.018). Conclusion: CVR impairment was found in approximately half of patients with unilateral MCA stenosis. Along with an increase in the degree of stenosis, patients with unilateral MCA stenosis were more likely to exhibit CVR impairment. It is important to assess the CVR in patients with unilateral MCA stenosis, especially those with severe stenosis.